The invisibile becomes visible: X-ray micro-CT reconstruction of Aneurus damzeni sp. nov. (Hemiptera: Heteroptera: Aradidae) from Eocene Baltic amber - Heiss, Ernst; Kairišs, Kristaps; Bukejs, Andris (Zootaxa, 2021)
The subfamily Aneurinae of the flat bug family Aradidae (Hemiptera: Heteroptera) contains about 150 extant species assigned to seven genera, and seven fossil species of which six were described from Eocene Baltic amber and one from Cretaceous Burmese amber. A new species Aneurus damzeni sp. nov. from Baltic amber is described and illustrated using X-ray micro-computed tomography (μCT) reconstructing concealed morphological characters. A key to all five extant and fossil Aneurinae species with triangular scutellum is provided.